A surface layer silicon source enrichment type ablation-resistant prepreg and a preparation method thereof
Patent Information
- Application Number
- CN202611046564.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-09-04
AI Technical Summary
[0007]本发明的目的在于克服现有技术存在的上述问题,提供一种表层硅源富集型耐烧蚀预浸料及其制备方法,以解决现有硼酚醛石英纤维类耐烧蚀预浸料在高温烧蚀过程中边缘区域与中心区域烧蚀程度差异较大的问题
1、本发明通过内浸渍液先浸渍石英纤维织物形成主体浸渍层,再采用含超细硅微粉的表层回润液处理双侧表面,使树脂主体浸渍和表层硅源布置分步完成。主体浸渍层能够先占据纤维束内部空间,表层回润液中的超细硅微粉更容易保留在双侧表层区域,有利于在烧蚀初期于外侧区域形成有效保护。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of ablation-resistant composite materials, and in particular to a surface silicon-rich ablation-resistant prepreg and its preparation method. Background Technology
[0002] Ablation-resistant resin-based composite materials are typically composed of a heat-resistant resin matrix and fiber reinforcement. They can delay heat transfer under high-temperature airflow, flame erosion, or short-term intense heat flow through resin pyrolysis, carbon layer formation, fiber skeleton support, and inorganic component melting protection. Therefore, they are often used in scenarios with high requirements for thermal protection performance, such as engine nozzles, heat insulation layers, and heat-resistant structural components.
[0003] Phenolic resins and their modified resins are widely used in ablation-resistant composite materials due to their high char residue, good thermal stability, and low cost. Boron-phenolic resins are modified resins formed by introducing boron into phenolic resins. Their cured products exhibit good char-forming ability and heat resistance at high temperatures and are often compounded with reinforcing materials such as quartz fibers and high-silica fibers to obtain prepregs or laminated composite materials suitable for high-temperature ablation environments.
[0004] In existing technologies, some solutions use high-silica fiber-reinforced modified phenolic resin to prepare prepregs and then hot-press them to obtain ablation-resistant composite materials. Other solutions use high-silica prepregs as the insulation layer for the back wall of the nozzle throat liner in solid rocket motors, improving the material's thermal insulation and molding properties by controlling indicators such as volatile matter, resin content, and soluble resin content. These solutions primarily focus on the overall heat resistance, overall ablation rate, thermal insulation performance, or lamination quality of the material, with insufficient attention paid to controlling the differences in ablation in localized areas during the ablation process.
[0005] In practical applications, when composite materials made from ablation-resistant prepregs are subjected to high-temperature airflow or flame erosion, the edges, corners, or exposed areas of the sample are often more susceptible to the combined effects of concentrated heat flow, enhanced oxygen diffusion, and char layer peeling than the central area. This leads to deeper ablation in the edge areas, resulting in uneven ablation depth distribution across different regions of the material. This issue affects the dimensional retention and service reliability of thermal protection structures, especially in thermal protection structures where high uniformity of localized ablation is required.
[0006] Therefore, it is still necessary to provide a method for preparing ablation-resistant prepreg to improve the problem of large differences in the degree of ablation between the edge and center regions of boron phenolic quartz fiber ablation-resistant prepreg during high-temperature ablation. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned problems in the prior art and provide a surface silicon-rich ablation-resistant prepreg and its preparation method, so as to solve the problem that the ablation degree of the edge area and the center area of the existing boron phenolic quartz fiber ablation-resistant prepreg is large during the high-temperature ablation process.
[0008] To achieve the above objectives, the first aspect of the present invention provides a method for preparing a surface silicon-rich ablation-resistant prepreg, comprising the following steps: S1: Mix boron phenolic resin, curing agent and solvent to obtain inner impregnation liquid; S2: The quartz fiber fabric is impregnated with the aforementioned internal impregnation solution and volatilized in parallel to form the main impregnation layer of the quartz fiber fabric; S3: Mix boron phenolic resin, ultrafine silica powder and solvent to obtain surface rewetting solution; S4: Apply the surface rewetting liquid to the surface of the quartz fiber fabric treated in step S2; S5: The quartz fiber fabric treated in step S4 is volatilized and cured to obtain an ablation-resistant prepreg. The ultrafine silica powder has a D50 particle size of 0.35 μm to 0.9 μm, and the amount of ultrafine silica powder added is 1.2% to 4.5% of the mass of boron phenolic resin in step S3. The ablation-resistant prepreg has a volatile content of 2.8% to 4.8%, a gum content of 34% to 43%, and a soluble resin content of 56% to 72%.
[0009] By first impregnating the quartz fiber fabric with an inner impregnation solution to form the main impregnation layer, and then treating the two main surfaces of the quartz fiber fabric opposite to each other in the thickness direction with a surface rewetting solution containing ultrafine silica powder, the interior of the quartz fiber fabric can be fully occupied by the boron phenolic resin system. Subsequently, the ultrafine silica powder in the surface rewetting solution is less likely to enter the depth of the fiber bundle in a disordered manner, but is more likely to be retained near the side surface of the prepreg.
[0010] The above treatment facilitates a more concentrated distribution of the silicon source in the outer region, which is the first to come into contact with the heat flow and oxidizing atmosphere during ablation. During ablation, the boron phenolic resin pyrolyzes to form a carbon layer and a boron-containing glassy phase precursor. The ultrafine silica powder enriched on the surface can participate in the borosilicate formation process at higher temperatures, enabling the outer region to form a relatively continuous and dense glassy protective layer earlier. Since the edge region is generally more susceptible to heat diffraction and oxygen diffusion, this surface silicon source enrichment structure allows the edge region to form a sealed protection more promptly, thereby improving the problem of large differences in ablation depth between the edge and center regions and resulting in a more uniform morphology after ablation.
[0011] Meanwhile, the D50 particle size of the ultrafine silica powder is controlled between 0.35 μm and 0.9 μm, which can balance the dispersion stability in the surface rewetting solution and the reactivity during ablation. When the particle size is too large, the suspension and spreading uniformity of the particles in the surface resin are easily reduced, and local silicon source insufficiency or particle agglomeration may occur; when the particle size is too small, the surface energy of the particles is high, and the viscosity and agglomeration tendency of the system will increase, which is not conducive to stable rewetting of both sides of the surface. In this invention, the amount of silica powder added is controlled to 1.2% to 4.5% of the mass of boron phenolic resin in step S3, which can provide sufficient surface silicon source without significantly disrupting the wetting continuity of boron phenolic resin on quartz fiber fabric, so that the prepreg maintains good process adaptability in subsequent lay-up and hot pressing.
[0012] Volatile matter, resin content, and soluble resin content collectively determine the processability of prepregs. When the volatile matter content is 2.8%–4.8%, the prepreg retains sufficient space for volatilization, preventing significant bubbling during subsequent hot pressing. When the resin content is 34%–43%, the resin can adequately coat the quartz fiber fabric while minimizing resin flow during hot pressing. When the soluble resin content is 56%–72%, the prepreg retains appropriate flow and compensation capacity in the initial stages of hot pressing, facilitating continuous bonding between the surface wetting area and the main impregnated layer, thereby reducing the tendency for delamination between the surface protective layer and the fiber reinforcement layer after ablation.
[0013] Preferably, in step S1, the viscosity of the inner impregnation solution at 25°C is 90 mPa·s to 220 mPa·s; in step S3, the viscosity of the surface rewetting solution at 25°C is 35 mPa·s to 95 mPa·s.
[0014] The inner impregnation solution uses a higher viscosity range, which is beneficial for forming a stable main impregnation layer inside the quartz fiber fabric, allowing the resin to maintain a certain occupancy between the fiber bundles. The surface rewetting solution uses a lower viscosity range, which is beneficial for its rapid spread on both sides of the surface and for carrying ultrafine silica powder into the surface resin area. The difference in viscosity between the two solutions means that the first impregnation is more focused on internal filling and skeleton formation, while the second rewetting is more focused on surface spreading and silica source arrangement.
[0015] Preferably, the viscosity ratio of the inner impregnation liquid at 25°C to the viscosity ratio of the surface rewetting liquid at 25°C is 1.8:1 to 4.5:1.
[0016] By limiting the viscosity ratio of the inner impregnation solution to the surface rewetting solution, the boundary between the two-step treatment can be further stabilized. The relatively high viscosity of the inner impregnation solution provides a certain degree of resistance after the main impregnation layer is formed; the relatively low viscosity of the surface rewetting solution allows it to form a more uniform rewetting layer on both surfaces. When the viscosity ratio is controlled within the above range, the surface rewetting solution can complete surface spreading without easily penetrating the already formed main impregnation layer in large quantities, thus achieving a more stable surface silicon source enrichment effect.
[0017] Preferably, in step S2, the evaporation temperature is 65℃~85℃, and the evaporation time is 8min~25min; in step S4, the unilateral application rate of the surface rewetting liquid is 8g / m 2 ~22g / m 2 .
[0018] The volatilization conditions in step S2 allow the main impregnated layer to reach a relatively stable solvent-containing state, reducing the degree of internal resin re-dilution during subsequent rewetting while preserving a certain interfacial bonding capacity. In step S4, the single-sided application rate of the surface rewetting solution is controlled at 8 g / m². 2 ~22g / m 2 This allows the ultrafine silica powder to achieve sufficient loading on both sides of the surface, while avoiding excessive application that could cause surface resin buildup, sagging, or localized particle deposition. Therefore, a good balance can be maintained between the surface silica source supply, resin continuity, and the surface condition of the prepreg.
[0019] Preferably, after step S4 and before step S5, the quartz fiber fabric treated in step S4 is subjected to evaporation at 75°C to 95°C for 6 min to 18 min.
[0020] This evaporation step can promptly increase the viscosity of the surface resin after the surface wetting solution has been spread, thus initially fixing the ultrafine silica powder in both surface areas. Since the main impregnation layer has already formed at this point, the solvent in the surface wetting solution is quickly drained, rapidly reducing the fluidity of the surface area and inhibiting the continued migration of the ultrafine silica powder inward. This process keeps the silicon source in a position more conducive to ablation protection.
[0021] Preferably, the boron content in the boron phenolic resin is 2.2% to 5.8% by mass; and the D90 particle size of the ultrafine silica powder is not greater than 1.8 μm.
[0022] The boron content is controlled between 2.2% and 5.8% by mass, providing a stable source of boron-containing glassy phase during the ablation process without making the resin system too brittle or the processing window too narrow. The D90 particle size of the ultrafine silica powder is no greater than 1.8 μm, reducing the impact of coarse particles on the uniformity of surface rewetting and allowing for a more continuous distribution of the silicon source on both sides of the surface. Under these particle size and content conditions, the boron and silicon sources more easily form a continuous borosilicate protective structure on the ablation surface, thereby improving the integrity of the surface carbonization protection.
[0023] Preferably, the mass ratio of boron in the boron phenolic resin to silicon in the ultrafine silica powder is 1:0.35 to 1:1.8; the ultrafine silica powder is a hydrophilic ultrafine silica powder, and the BET specific surface area of the ultrafine silica powder is 80 m². 2 / g~260m 2 / g.
[0024] By limiting the boron-to-silicon mass ratio within the aforementioned range, a good compatibility can be maintained between the boron-containing glassy phase precursor formed by the boron phenolic resin during ablation and the ultrafine silica powder introduced by the surface wetting solution. If the silicon ratio is too low, there will be insufficient silicon source in the surface region to participate in borosilicate formation, resulting in insufficient continuity of the glassy protective structure formed in the early stages of ablation. If the silicon ratio is too high, the excessive content of inorganic particles in the surface layer can easily affect the continuous coating of the boron phenolic resin on the quartz fiber fabric surface and subsequent hot-pressing bonding. Controlling the boron-to-silicon mass ratio to 1:0.35–1:1.8 allows the surface region to maintain resin phase continuity while providing sufficient silicon source to participate in the high-temperature borosilicate formation process, thus facilitating the formation of a more complete and stable surface protective structure.
[0025] Hydrophilic ultrafine silica powder was used, and its BET specific surface area was controlled to be 80m². 2 / g~260m 2 The concentration of / g can further improve the dispersion and interfacial contact of ultrafine silica powder in the surface rewetting solution. Hydrophilic ultrafine silica powder typically has numerous polar groups such as silanol groups on its surface, enabling it to form good wetting contact with the boron-phenolic resin system. This ensures that the ultrafine silica powder is not simply deposited as inert particles on the surface, but rather more uniformly distributed within the surface resin phase. When the BET specific surface area is within the aforementioned range, the particles possess sufficient surface activity and contact area, which is beneficial for achieving adequate contact between the boron and silicon sources during the ablation stage; simultaneously, it avoids significantly increasing the system viscosity or enhancing the tendency to agglomerate due to excessively high specific surface area. This achieves a better balance between the construction stability of the surface rewetting solution, the surface retention of the ultrafine silica powder, and the glass transition protection reaction during the ablation stage.
[0026] Preferably, in step S5, the curing temperature is 85℃~110℃ and the curing time is 6min~20min.
[0027] The curing process further enhances the viscosity and structural stability of the boron phenolic resin system in the surface rewetting zone, making it less prone to significant re-migration of the surface ultrafine silica powder during storage, transportation, and subsequent hot pressing. Controlling the curing temperature and time within the aforementioned range achieves moderate thickening and structural fixation while preserving the flowability required for subsequent hot pressing of the prepreg. This maintains the enriched silica source on the surface while avoiding a decrease in prepreg layability and interlayer bonding due to over-curing.
[0028] Preferably, in step S5, the curing temperature is 10°C to 40°C lower than the gel temperature of the boron phenolic resin system.
[0029] Controlling the curing temperature to 10°C–40°C below the gel temperature of the boron phenolic resin system allows the surface rewetting area to enter a viscous but not fully gelled state. In this state, the resin molecular chain mobility decreases, and the ultrafine silica powder is more stably maintained in the surface region; simultaneously, the resin system does not completely lose its flow and cross-linking capabilities for subsequent hot pressing. Therefore, this curing condition achieves a balance between the spatial distribution stability of the silica powder and the subsequent molding density. More importantly, it addresses the specific process problem of particle re-migration after surface rewetting, allowing the surface silica source enrichment state to continue from the preparation stage to the final hot pressing stage.
[0030] A second aspect of the present invention provides an ablation-resistant prepreg, which is prepared by the preparation method described above.
[0031] In the ablation-resistant prepreg prepared by the above method, a continuous bond can be formed between the main impregnation layer and the surface rewetting layer, and ultrafine silica powder is more easily retained in both surface areas. During the ablation process, the outer region of this prepreg can form a borosilicate glassy protective structure earlier, improving the integrity and erosion resistance of the carbon layer in the edge region, thereby reducing the ablation difference between the edge region and the center region after ablation. Overall, this prepreg not only possesses the heat resistance and carbonization basis of the boron phenolic quartz fiber system itself, but also, through the controlled arrangement of the surface silicon source, allows the ablation protection effect to be more concentrated in the area most directly affected by heat flow and oxidation environment.
[0032] The present invention, by adopting the above technical solution, has the following beneficial effects: 1. This invention first impregnates the quartz fiber fabric with an internal impregnation liquid to form the main impregnation layer, and then treats both sides of the surface with a surface rewetting liquid containing ultrafine silica powder. This allows the resin main impregnation and the surface silica source arrangement to be completed in steps. The main impregnation layer can occupy the internal space of the fiber bundle first, and the ultrafine silica powder in the surface rewetting liquid is more easily retained in the surface areas on both sides, which is beneficial for forming effective protection in the outer area during the early stage of ablation.
[0033] 2. This invention controls the particle size and dosage of ultrafine silica powder, as well as the application method of the surface wetting solution, to ensure that the ultrafine silica powder maintains good dispersion and spreading in the surface wetting solution without significantly disrupting the continuous coating of boron phenolic resin onto the quartz fiber fabric. The resulting prepreg exhibits good layability, resin stability, and adaptability to subsequent hot pressing.
[0034] 3. This invention controls the mass ratio of boron in boron phenolic resin to silicon in ultrafine silica powder, and uses hydrophilic ultrafine silica powder with a specific BET surface area, so that the boron source and silicon source in the surface area have a better contact and reaction basis during high-temperature ablation, which is conducive to the formation of a more continuous borosilicate protective structure and improves the integrity and erosion resistance of the surface carbonization protection.
[0035] 4. This invention, through process control of volatilization, maturation, and a certain range below the gel temperature, allows the resin system to become moderately viscous but not completely gel after the surface rewetting liquid has been spread. This reduces the tendency of ultrafine silica powder to migrate again during storage, transportation, and subsequent hot pressing, while retaining the flow and cross-linking capabilities required for hot pressing. This is beneficial for balancing the preservation of the surface silicon source and the interlayer bonding strength.
[0036] 5. During the ablation process, the ablation-resistant prepreg prepared by this invention can form a borosilicate-containing glassy protective structure on the outer surface layer earlier, which is particularly beneficial for improving the problem of localized ablation deepening caused by heat diffraction and oxygen diffusion in the edge area. This prepreg can reduce the ablation difference between the edge area and the center area, making the morphology more uniform after ablation and improving the integrity of the carbon layer. Detailed Implementation
[0037] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0038] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0039] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0040] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0041] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0042] Unless otherwise specified, all parts in the following examples and comparative examples are parts by weight. The quartz fiber fabric used is plain-weave quartz fiber cloth with an areal density of 240 g / m². 2 The thickness is 0.22 mm, and the SiO2 content is not less than 99%. The boron phenolic resin is a soluble thermosetting boron phenolic resin with a softening point of 85℃, a free phenol content of 5.6%, and a moisture content of 1.1%. Hexamethylenetetramine is used as the curing agent. Anhydrous ethanol and acetone are mixed solvents in a mass ratio of 72:28. The ultrafine silica powder is a hydrophilic silica powder. Viscosity was measured using a rotational viscometer at 25℃ with a rotor speed of 60 r / min. The gel temperatures listed below are the gel temperatures of the resin system formed after the surface wetting liquid has been desolventized. The gel temperatures were determined using the hot-stage method, with the temperature at which the resin system loses its fluidity during the heating process taken as the gel temperature.
[0043] Example 1: This example discloses a method for preparing a surface silicon-rich ablation-resistant prepreg, comprising the following steps: S1: Take 100 parts of boron phenolic resin with a boron content of 4.0%, add 9 parts of hexamethylenetetramine, and then add 118 parts of mixed solvent. Stir at 600 r / min for 45 min at 25℃ to obtain the inner impregnation solution. The viscosity of the inner impregnation solution at 25℃ is 157 mPa·s.
[0044] S2: Cut the quartz fiber fabric into 300mm×300mm sheets, immerse the sheets completely in the inner impregnation solution for 5 minutes, and then squeeze the excess resin solution through a two-roller extrusion device at a pressure of 0.12MPa. Afterwards, place the impregnated quartz fiber fabric in a 75℃ hot air oven for 16 minutes to allow the quartz fiber fabric to form the main impregnation layer.
[0045] S3: Take 100 parts of boron phenolic resin with a boron content of 4.0% by mass. Based on the mass of this boron phenolic resin, add particles with a D50 particle size of 0.55 μm, a D90 particle size of 1.2 μm, and a BET specific surface area of 162 m². 2 3.2 parts of hydrophilic ultrafine silica powder per g were added, along with 165 parts of mixed solvent. The mixture was dispersed at 1200 r / min for 30 min at 25 °C, and then ultrasonically dispersed at 400 W for 10 min to obtain the surface wetting solution.
[0046] The viscosity of the surface wetting solution at 25°C is 65 mPa·s. The mass ratio of boron in the boron phenolic resin to silicon in the ultrafine silica powder is 1:0.37.
[0047] S4: Apply the surface rewetting liquid to two opposite surfaces along the thickness direction of the quartz fiber fabric treated in step S2 using a scraping method. The application amount on each side is 15 g / m². 2 After application, let stand at 25°C for 2 minutes to allow the surface wetting liquid to spread on both sides of the surface.
[0048] S5: The quartz fiber fabric treated in step S4 is placed in an 85℃ hot air oven for 12 minutes to evaporate, and then cured at 100℃ for 12 minutes to obtain an ablation-resistant prepreg.
[0049] The resin system formed after removing the solvent using the surface rewetting solution in step S5 has a gel temperature of 132.4℃, and its curing temperature is 32.4℃ lower than the gel temperature. The volatile matter content of the ablation-resistant prepreg is 3.6%, the gum content is 39.2%, and the soluble resin content is 64.8%.
[0050] Example 2 discloses a method for preparing a surface silicon-rich ablation-resistant prepreg, which differs from Example 1 in that: In step S3, the hydrophilic ultrafine silica powder has a D50 particle size of 0.42 μm, a D90 particle size of 0.96 μm, and a BET specific surface area of 118 m². 2 / g, the amount added is 3.3 parts; the viscosity of the surface wetting liquid at 25℃ is 58mPa·s; the mass ratio of boron in boron phenolic resin to silicon in ultrafine silica powder is 1:0.38.
[0051] In step S4, the amount of surface rewetting fluid applied on one side is 10 g / m². 2 .
[0052] In step S5, the resin is volatilized at 85°C for 10 minutes and cured at 100°C for 10 minutes. The resin system formed after solvent removal using the surface rewetting solution in step S5 has a gel temperature of 131.6°C, and the curing temperature is 31.6°C lower than the gel temperature. The resulting ablation-resistant prepreg has a volatile content of 3.9%, a resin content of 37.2%, and a soluble resin content of 67.4%.
[0053] Example 3 discloses a method for preparing a surface silicon-rich ablation-resistant prepreg, which differs from Example 1 in that: In step S3, the hydrophilic ultrafine silica powder has a D50 particle size of 0.82 μm, a D90 particle size of 1.63 μm, and a BET specific surface area of 213 m². 2 / g, the amount added is 4.3 parts; the viscosity of the surface wetting liquid at 25℃ is 88mPa·s; the mass ratio of boron in boron phenolic resin to silicon in ultrafine silica powder is 1:0.50.
[0054] In step S4, the amount of surface rewetting fluid applied on one side is 21 g / m². 2 .
[0055] In step S5, the resin is volatilized at 90℃ for 16 min and cured at 105℃ for 15 min. The resin system formed after solvent removal using the surface rewetting solution in step S5 has a gel temperature of 133.7℃, and the curing temperature is 28.7℃ lower than the gel temperature. The resulting ablation-resistant prepreg has a volatile content of 3.0%, a resin content of 42.1%, and a soluble resin content of 58.6%.
[0056] Example 4 discloses a method for preparing a surface silicon-rich ablation-resistant prepreg, which differs from Example 1 in that: In step S2, the volatilization temperature is 70℃ and the volatilization time is 22min.
[0057] In step S5, the quartz fiber fabric treated in step S4 is first volatilized at 80°C for 15 minutes, and then cured at 92°C for 18 minutes. The resin system formed after removing the solvent from the surface rewetting solution used in step S5 has a gel temperature of 131.7°C, and the curing temperature is 39.7°C lower than the gel temperature. The resulting ablation-resistant prepreg has a volatile content of 3.9%, a resin content of 38.5%, and a soluble resin content of 66.1%.
[0058] Example 5 discloses a method for preparing a surface silicon-rich ablation-resistant prepreg, which differs from Example 1 in that: In steps S1 and S3, the boron content of the boron phenolic resin is 2.8% by mass.
[0059] In step S3, the hydrophilic ultrafine silica powder has a D50 particle size of 0.60 μm, a D90 particle size of 1.35 μm, and a BET specific surface area of 226 m². 2 / g, the amount added is 4.2 parts; the viscosity of the surface wetting liquid at 25℃ is 84mPa·s; the mass ratio of boron in boron phenolic resin to silicon in ultrafine silica powder is 1:0.70.
[0060] In step S4, the application rate of the surface rewetting solution on one side is 18 g / m². 2 .
[0061] In step S5, the resin is volatilized at 88℃ for 14 minutes and cured at 98℃ for 16 minutes. The resin system formed after solvent removal using the surface rewetting solution in step S5 has a gel temperature of 130.6℃, and the curing temperature is 32.6℃ lower than the gel temperature. The resulting ablation-resistant prepreg has a volatile content of 3.4%, a resin content of 40.3%, and a soluble resin content of 61.7%.
[0062] Comparative Example 1 This comparative example discloses a method for preparing an ablation-resistant prepreg, which differs from Example 1 in that: In step S1, the particle size of D50 is 0.55 μm, the particle size of D90 is 1.2 μm, and the BET specific surface area is 162 m². 2 3.2 parts of hydrophilic ultrafine silica powder (g / g) were directly added to the internal impregnation solution and dispersed at 1200 r / min for 30 min, followed by ultrasonic dispersion at 400 W for 10 min. Then, a mixed solvent was added to adjust the viscosity, resulting in an internal impregnation solution containing ultrafine silica powder. The viscosity of the internal impregnation solution containing ultrafine silica powder at 25 °C was 162 mPa·s.
[0063] In step S3, no ultrafine silica powder is added. Instead, 100 parts of boron phenolic resin with a boron content of 4.0% and 165 parts of mixed solvent are mixed and stirred evenly to form the surface wetting solution.
[0064] The other steps and parameters were the same as in Example 1. The resulting ablation-resistant prepreg had a volatile content of 3.7%, a gum content of 39.0%, and a soluble resin content of 64.2%.
[0065] Comparative Example 2 This comparative example discloses a method for preparing an ablation-resistant prepreg, which differs from Example 1 in that: In step S3, without adding ultrafine silica powder, only 100 parts of boron phenolic resin with a boron content of 4.0% and 165 parts of mixed solvent are taken and stirred at 600 r / min for 30 min at 25°C to obtain the surface wetting solution. The viscosity of the surface wetting solution at 25°C is 49 mPa·s.
[0066] The other steps and parameters were the same as in Example 1. The resulting ablation-resistant prepreg had a volatile content of 3.8%, a gum content of 38.7%, and a soluble resin content of 65.0%.
[0067] Comparative Example 3 This comparative example discloses a method for preparing an ablation-resistant prepreg, which differs from Example 1 in that: In step S5, the quartz fiber fabric treated in step S4 is placed in an 85°C hot air oven for 12 minutes to evaporate, and then cooled directly to 25°C and wound up without undergoing 100°C curing treatment to obtain an ablation-resistant prepreg.
[0068] The other steps and parameters were the same as in Example 1. The resulting ablation-resistant prepreg had a volatile content of 4.2%, a gum content of 39.4%, and a soluble resin content of 70.6%.
[0069] Comparative Example 4 This comparative example discloses a method for preparing an ablation-resistant prepreg, which differs from Example 1 in that: In step S3, the hydrophilic ultrafine silica powder is replaced with low specific surface area fused silica powder. The low specific surface area fused silica powder has a D50 particle size of 2.48 μm, a D90 particle size of 5.76 μm, and a BET specific surface area of 18.4 μm. 2 / g, the amount added is 3.2 parts. The viscosity of the surface rewetting solution at 25℃ is 57 mPa·s.
[0070] The other steps and parameters were the same as in Example 1. The resulting ablation-resistant prepreg had a volatile content of 3.5%, a gum content of 39.1%, and a soluble resin content of 63.9%.
[0071] Performance testing The ablation-resistant prepregs and their hot-pressed cured composites prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance testing.
[0072] The hot-press curing conditions are as follows: the ablation-resistant prepreg is laid in alternating layers at 0° / 90° until the thickness is 6.0 mm. First, it is heated at 135°C and 0.6 MPa for 30 min for low-pressure volatilization, and then heated at 175°C and 4.0 MPa for 120 min for densification curing. After cooling to below 60°C, it is demolded to obtain the ablation-resistant composite material sample.
[0073] 1. Testing of volatile matter, gum content, and soluble resin content in prepregs The volatile matter content of the prepreg was tested according to GB / T 32788.3-2016 "Test Methods for Performance of Prepregs - Part 3: Determination of Volatile Matter Content"; the resin content was tested according to GB / T 32788.5-2016 "Test Methods for Performance of Prepregs - Part 5: Determination of Resin Content". The soluble resin content was determined using the acetone extraction method. Approximately 2g of prepreg sample was accurately weighed and refluxed in acetone for 2 hours. After extraction, the sample was dried at 80℃ to constant weight. The soluble resin content was calculated based on the proportion of resin that could be extracted by acetone before extraction to the total resin mass in the prepreg. Each sample was tested in triplicate, and the average value was taken.
[0074] Table 1. Test results of basic properties of prepreg
[0075] As shown in Table 1, the volatile matter, adhesive content, and soluble resin content of Examples 1-5 are all within the range suitable for prepreg laying and hot pressing, indicating that the two-step impregnation, surface rewetting, and curing treatments did not compromise the basic process applicability of the prepreg. Comparative Example 3, which did not undergo curing treatment, had a relatively high soluble resin content and surface viscosity, indicating that the curing step could moderately increase the viscosity of the surface rewetting area and improve the stability of the prepreg.
[0076] 2. Particle size and BET specific surface area detection The particle size of ultrafine silica powder and low specific surface area fused silica powder was determined according to GB / T 19077-2024 "Particle Size Analysis by Laser Diffraction Method". Anhydrous ethanol was used as the dispersion medium, and the powder was ultrasonically dispersed for 3 minutes before testing. The BET specific surface area was determined according to GB / T19587-2017 "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method". The sample was degassed under vacuum at 120℃ for 2 hours before testing. Each sample was tested in triplicate, and the average value was taken.
[0077] Table 2. Results of silicon micropowder particle size and BET specific surface area.
[0078] As shown in Table 2, the hydrophilic ultrafine silicon powder used in the examples has a smaller particle size and a higher BET specific surface area, which is beneficial for forming a more stable dispersion in the surface wetting solution and providing a larger contact interface between the boron source and silicon source during the ablation stage. In contrast, the low specific surface area molten silicon powder used in Comparative Example 4 has a significantly larger particle size and a lower specific surface area, making it more prone to localized particle enrichment in the surface wetting solution and difficult to form a continuous and uniform glass transition protective structure during subsequent ablation.
[0079] Surface silicon source retention test To evaluate the retention of ultrafine silica powder in the surface region after surface rewetting, the prepregs prepared in Examples 1-5 and Comparative Examples 1, 3, and 4 were placed in an environment of 25°C and 50% relative humidity for 7 days, and then 30mm × 30mm samples were cut from each sample. Energy-dispersive X-ray fluorescence spectrometry was used to detect the relative signal intensity of Si element on both sides of the sample surface. Five test points were taken on each side of each sample, and the average value of both sides was recorded. The relative signal intensity of surface Si element immediately after preparation in Example 1 was taken as 100%, and the relative retention rate of surface Si element after 7 days of storage was calculated. Comparative Example 2 did not contain silica powder and was not included in this comparison.
[0080] Table 3. Surface Silicon Source Retention Test Results
[0081] As shown in Table 3, after curing treatment, the relative signal intensity of Si on the surface of Examples 1-5 remained above 85% after 7 days of storage. This indicates that the curing process can increase the viscosity of the resin system after the surface rewetting liquid has completed spreading, thereby reducing the tendency for ultrafine silicon powder to continue migrating inward or locally detaching. Although the total amount of silicon powder in Comparative Example 1 was similar to that in Example 1, the relative signal intensity of Si on the surface was significantly lower after adding silicon powder to the inner impregnation liquid, indicating that the silicon source was not effectively arranged in the surface area. Comparative Example 3 did not undergo curing treatment, and the retention rate of the surface silicon source decreased significantly, indicating that directly winding after surface rewetting is not conducive to the stable retention of the surface silicon source. Comparative Example 4 used low specific surface area molten silicon powder, and the surface signal retention and uniformity were poor, indicating that particle size and specific surface area have an impact on the stable arrangement of the surface silicon source.
[0082] Interlaminar shear strength testing The prepregs obtained in Examples 1-5 and Comparative Examples 1-4 were used to prepare composite material sheets under the above-described hot-pressing curing conditions. Interlaminar shear strength was tested according to GB / T 1450.1-2005 "Test Method for Interlaminar Shear Strength of Fiber Reinforced Plastics". The sample size was the same as that of a short beam shear sample, the loading speed was 2 mm / min, and 5 samples were tested in each group, with the average value taken.
[0083] Table 4. Results of interlaminar shear strength testing
[0084] As shown in Table 4, the interlaminar shear strength of Examples 1-5 remained above 30 MPa, indicating that the introduction of ultrafine silica powder during surface rewetting did not significantly weaken the interlaminar bond between the quartz fiber fabric and the boron phenolic resin system. Comparative Example 3, which was not cured, was more prone to localized porosity and interface inhomogeneity during subsequent hot pressing; Comparative Example 4 used molten silica powder with a larger particle size and low specific surface area, and localized particle agglomeration negatively impacted the interlaminar bond.
[0085] 5. Oxyacetylene ablation performance testing The ablation performance was tested for oxyacetylene ablation in accordance with GJB 323A-1996 "Test Method for Ablation of Ablation Materials". In addition, based on the edge ablation uniformity that this invention is concerned with, the ablation depth in the central region of the sample, the ablation depth in the region 5 mm from the edge of the sample, and the difference in ablation depth between the edge and the center were further measured.
[0086] The hot-pressed and cured composite material sheets were processed into 50mm×50mm×6mm specimens, with the ablation surface being one of the two surfaces of the prepreg. The oxygen pressure was 0.40MPa, the acetylene pressure was 0.095MPa, the distance from the nozzle outlet to the specimen surface was 10mm, and the ablation time was 60s. After ablation, the specimens were cooled to room temperature, and the ablation depth in the central region and the region 5mm from the edge were measured. For each specimen, three points were taken in the central region and three points on each of the four edges. The difference between the average ablation depth in the edge region and the average ablation depth in the central region was calculated. Three specimens were tested in each group, and the average value was taken.
[0087] Table 5 Results of Oxyacetylene Ablation Performance Test
[0088] As shown in Table 5, the linear ablation rate and mass ablation rate of Examples 1-5 were both low, and the ablation depth difference between the edge and center was controlled within 0.42 mm to 0.51 mm, while the edge peeling length was controlled within 1.8 mm to 2.4 mm. This indicates that by constructing the main impregnation layer and the surface wetting solution in stages, combined with hydrophilic ultrafine silica powder and aging treatment below the gel temperature, a relatively complete borosilicate glassy protective structure can be formed in the surface area during the ablation process, which is particularly beneficial for suppressing the local ablation deepening in the edge area. In Comparative Example 1, ultrafine silica powder was directly added to the inner impregnation solution, resulting in insufficient surface silica source and an increased ablation depth difference between the edge and center; in Comparative Example 2, no ultrafine silica powder was added, and the ablation deepening in the edge area was the most obvious; in Comparative Example 3, no aging was performed, resulting in decreased surface silica source retention and increased ablation unevenness; in Comparative Example 4, low specific surface area molten silica powder was used, resulting in insufficient continuity of the surface protective structure and a large edge peeling length.
[0089] Temperature rise detection after ablation During the oxyacetylene ablation test, a type K thermocouple was fixed at the center of the unexposed surface of the sample. The temperature of the unexposed surface was recorded after 60 seconds of ablation and the highest temperature of the unexposed surface within 30 seconds after the ablation ended. Three samples were tested in each group, and the average value was taken.
[0090] Table 6. Results of back temperature rise detection after ablation
[0091] As shown in Table 6, the back-exposed surface temperature was lower in Examples 1-5 during the ablation process, indicating that the surface borosilicate glass protective structure and the intact carbon layer can slow down the heat transfer to the back-exposed surface. Combined with the ablation depth and edge spalling results in Table 5, it can be seen that the ablation-resistant prepreg prepared by this invention not only improves the uniformity of edge ablation but also maintains good thermal insulation protection.
[0092] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a surface silicon-rich ablation-resistant prepreg, characterized in that, Includes the following steps: S1: Mix boron phenolic resin, curing agent and solvent to obtain inner impregnation liquid; S2: The quartz fiber fabric is impregnated with the aforementioned internal impregnation solution and volatilized in parallel to form the main impregnation layer of the quartz fiber fabric; S3: Mix boron phenolic resin, ultrafine silica powder and solvent to obtain surface rewetting solution; S4: Apply the surface rewetting liquid to the surface of the quartz fiber fabric treated in step S2; S5: The quartz fiber fabric treated in step S4 is volatilized and cured to obtain an ablation-resistant prepreg. The ultrafine silica powder has a D50 particle size of 0.35 μm to 0.9 μm, and the amount of ultrafine silica powder added is 1.2% to 4.5% of the mass of boron phenolic resin in step S3. The ablation-resistant prepreg has a volatile content of 2.8% to 4.8%, a gum content of 34% to 43%, and a soluble resin content of 56% to 72%.
2. The preparation method according to claim 1, characterized in that, In step S1, the viscosity of the inner impregnation solution at 25°C is 90 mPa·s to 220 mPa·s; in step S3, the viscosity of the surface rewetting solution at 25°C is 35 mPa·s to 95 mPa·s.
3. The preparation method according to claim 2, characterized in that, The viscosity ratio of the inner impregnation solution at 25°C to that of the surface rewetting solution at 25°C is 1.8:1 to 4.5:
1.
4. The preparation method according to claim 1, characterized in that, In step S2, the evaporation temperature is 65℃~85℃, and the evaporation time is 8min~25min; in step S4, the unilateral application rate of the surface rewetting liquid is 8g / m 2 ~22g / m 2 .
5. The preparation method according to claim 1, characterized in that, After step S4 and before step S5, the quartz fiber fabric treated in step S4 is subjected to evaporation at 75℃~95℃ for 6min~18min.
6. The preparation method according to claim 1, characterized in that, The boron content in the boron phenolic resin is 2.2% to 5.8% by mass; the D90 particle size of the ultrafine silica powder is no greater than 1.8 μm.
7. The preparation method according to claim 1, characterized in that, The mass ratio of boron in the boron phenolic resin to silicon in the ultrafine silica powder is 1:0.35 to 1:1.8; the ultrafine silica powder is a hydrophilic ultrafine silica powder with a BET specific surface area of 80 m². 2 / g~260m 2 / g.
8. The preparation method according to claim 1, characterized in that, In step S5, the curing temperature is 85℃~110℃, and the curing time is 6min~20min.
9. The preparation method according to claim 8, characterized in that, In step S5, the curing temperature is 10°C to 40°C lower than the gel temperature of the boron phenolic resin system.
10. An ablation-resistant prepreg, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.